Characterising trauma‐informed aged care: An appreciative inquiry approach. (26th August 2022) - de la Perrelle, Lenore; Klinge, Nathan; Windsor, Tim; Low, Lee‐Fay; Laver, Kate; Cations, Monica
Abstract: Objective: While Trauma‐informed care (TIC) has the potential to improve the quality of aged and dementia care, the challenge remains in translating the principles of TIC into practice. This study aimed to characterise what trauma‐informed aged care looks like in practice, by learning from an aged care service acknowledged as delivering trauma‐informed aged care effectively. Method: We conducted an appreciative inquiry study within a residential aged care service catering for veterans and others with trauma histories. Observation of care behaviours, interviews with staff and residents, and organisational policy mapping were used to identify elements that maximised care safety and accessibility for trauma survivors. Data were analysed and triangulated using a framework analysis approach. Results: The aged care provider embedded the principles of TIC into its staff training (i) to promote understanding of how trauma may affect experiences in care, and (ii) to adapt care when appropriate to promote safety. The service promoted a calm atmosphere where residents could make choices and felt safe. Uniforms and signage provided consistency, clarity, and transparency for residents. Staff behaviours demonstrated respect, fostered trust, and anticipated needs without unnecessarily imposing care. Staff consistently offered choices, used residents' names, sought permission before providing care, and offered reassurance. Staff reported high morale with a commitment to delivering high quality care, and feedback to management. Effective communication promoted information sharing and trust among staff. Conclusion: Trauma‐informed practice was facilitated through organisational policy, a dignified environment, and thoughtful staff behaviour creating safety, choice, and control for residents. Key points: Trauma‐informed care (TIC) is poorly characterised in aged care and staff require guidance in how to amend everyday practice to meet the needs of trauma survivors. Principles of TIC need to be embedded into organisational policy, procedures, and in staff training and mentoring to adapt care. Environmental elements demonstrated transparency of policy to service users and staff and enabled a sense of dignity for residents. Consistent respectful behaviour, kindness and sensitive understanding of needs fostered trust between residents and staff and information sharing between staff.